Akseptabilitas Draf Kriteria Baru Penentuan Kalender Hijriah Menurut Ahli Falak di Indonesia - Fadholi, Ahmad (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2019)
In 2015 AD, 2016 AD, 2017 and 2017 there was a new discussion about the draft of new criteria for the determination of the Islamic calendar in Indonesia, namely the draft MUI criteria and the new draft criteria MABIMS, with the criteria of 3 degrees hilal height and 6.4 degree elongation. This criterion is deliberately made for the benefit and mutual agreement for the unification of the hijri calendar in Indonesia. It is hoped that the experts of the Islamic organizations in Indonesia will give their views and attitudes to the draft of new criteria to harmonize the criteria for "hilal visibility" which will be used as a reference and guideline for the determination of the beginning of the Islamic month. This study shows that both the rukyat school and the reckoning school as a whole are acceptable for the draft MUI criteria and the new draft MABIMS as the determination of the Islamic calendar in Indonesia. However, overall the distribution of the scores of the two schools is categorized as moderate, so there are those who agree, disagree, and do not agree with the draft criteria. Overall, the two new draft criteria have the opportunity to be applied in Indonesia. To realize this, it is necessary to have a dialogue between Islamic mass organizations, astronomers and fiqh experts, as well as the government as policy makers.